2001
DOI: 10.1046/j.1525-1594.2001.025003172.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Tissue Engineering Technique for Repair of Cartilage Defect

Abstract: Hunter's observation in 1743 that cartilage "once destroyed, is not repaired," has not essentially changed for 250 years. At present, there is no well-established procedure for the repair of cartilage defect with articular cartilage, which has the same biochemical and biomechanical properties as the surrounding normal intact cartilage. In 1994, transplantation of human autologous chondrocytes in suspension, as reported by Brittberg et al., provided a potential procedure for articular cartilage repair. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 21 publications
3
115
0
2
Order By: Relevance
“…It has been reported that nanoporous or nano-fibrous polymer matrices played a critical role in providing support and anchorage for cells, while maintaining chondrocyte phenotype and enhancing chondrocyte growth and matrix synthesis Li et al, 2006). The fabrication technologies used for scaffold fabrication in cartilage tissue engineering included electrospinning (Wise et al, 2009), particulate leaching combined with chemical etching Park et al, 2005) and 3-D printing techniques (Yen et al, 2009). L-L TIPS is an easy and effective technique to fabricate 3D nano-fibrous scaffolds (Ma, 2008;Zhang and Ma, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nanoporous or nano-fibrous polymer matrices played a critical role in providing support and anchorage for cells, while maintaining chondrocyte phenotype and enhancing chondrocyte growth and matrix synthesis Li et al, 2006). The fabrication technologies used for scaffold fabrication in cartilage tissue engineering included electrospinning (Wise et al, 2009), particulate leaching combined with chemical etching Park et al, 2005) and 3-D printing techniques (Yen et al, 2009). L-L TIPS is an easy and effective technique to fabricate 3D nano-fibrous scaffolds (Ma, 2008;Zhang and Ma, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, cartilage repair and regeneration are major challenges despite recent progress in orthopedic surgery, because the lesions do not spontaneously heal and their consequences have a significant social and economic impact (Brooks et al, 2002;Sellards et al, 2002). The tissue engineering strategy provides a promising therapy to repair cartilage defects and restore joint functions (Stoddart et al, 2009;Ochi et al, 2001;Cancedda et al, 2003;Tuli et al, 2003). A three-dimensional (3D) scaffold is employed for delivery or recruitment of reparative cells in an organized manner to bridge voids within cartilage defects, offering considerable promise as repair strategies (Solchaga et al, 2001;Grande et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The material has an advantage in generating 3D structure of implant. Ochi et al [143,144] have applied the aterocollagen as a carrier of chondrocytes in ACI. However, when implanted, the ateloacollagen-cell composites should be covered with periosteum not to be detached from implantation sites [145].…”
Section: Scaffolds For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…For example, Dr. Ochi Mitsuo in Japan had used atelocollagen as a scaffold to carry autogenous chondrocytes in the treatment of 51 patients with osteochondral lesions. The clinical results were promising [75]. In Italy, Professor Paolo Cherubino in University of Insubria had conducted a 13 patients clinical trial with matrix-induced autologous chondrocytes implantation using a bilayer collagen membrane (MACI; Verigen, Leverkusen, Germany).…”
Section: Clinical Trial Study Of Cartilage Tissue Engineeringmentioning
confidence: 99%